Papers Presented at the Seventh Workshop on Empirical Studies of Programmers - ESP '97 1997
DOI: 10.1145/266399.266414
|View full text |Cite
|
Sign up to set email alerts
|

Program understanding behavior during debugging of large scale software

Abstract: This paper reports on a software understanding experiment during corrective maintenance of large-scale software. Participants were professional software maintenance engineers. The paper reports on the general understanding process, the types of actions programmers preferred during the debugging task, and the level of abstraction at which they were working. The results of the observation are also interpreted in terms of the information needs of these software engineers during the debugging task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…We believe that this is the cause of the large gap in the performance of novices and experts. This coincides with the work of von Mayrhauser and Vans [12], who found that programmers who have more domain knowledge would perform program comprehension at a higher-level abstraction. In terms of our case study, a novice might have trouble identifying the cause of the slow response to SQL query whereas an expert immediately recognizes it as the problem of creating child process.…”
Section: Discussionsupporting
confidence: 89%
“…We believe that this is the cause of the large gap in the performance of novices and experts. This coincides with the work of von Mayrhauser and Vans [12], who found that programmers who have more domain knowledge would perform program comprehension at a higher-level abstraction. In terms of our case study, a novice might have trouble identifying the cause of the slow response to SQL query whereas an expert immediately recognizes it as the problem of creating child process.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the programmer must continually switch between writing new code and understanding existing code, possibly constructed by other persons. Extensive research has aimed to find ways of supporting the programmer in these activities [11,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…(The notable exception is the use of bug tracking in detailing a theory of coordination mechanisms [36].) The debugging process also has been used to probe other issues in software development, such as von Mayrhauser and Vans' [29] discussion of program understanding.…”
Section: Change Managementmentioning
confidence: 99%